The Use of Geographical Information System in Visual Fishery Information in East Java - M. Basuki Rahmat; Farizi Rachman; R. A. Norromadani Yuniati; Ryan Yudha Aditya (THE SPIRIT OF SOCIETY JOURNAL : International Journal of Society Development and Engagement, 2023)
This article presents considerations made to show how important it is to use current information to help make a decision. we are currently faced with major social and technological challenges. The main purpose of this discussion is to gain knowledge about the level of use of information technology to create geographic information systems or visual maps of fishery potential in East Java and advantages of GIS in fishing industry. Studies are based on the idea of the need to implement measures aimed at the development and enhancement of fishery potential. The methodological basis for the discussion is an analysis of the literature and case studies.